A Wars2 mutant mouse shows a sex and diet specific change in fat distribution, reduced food intake and depot-specific upregulation of WAT browning - Mušo, Milan; Bentley, Liz; Vizor, Lucie; Yon, Marianne; Burling, Keith; Barker, Peter; Zolkiewski, Louisa A. K.; Cox, Roger D.; Dumbell, Rebecca (Frontiers in Physiology, 2022)
Background: Increased waist-to-hip ratio (WHR) is associated with increased mortality and risk of type 2 diabetes and cardiovascular disease. The TBX15-WARS2 locus has consistently been associated with increased WHR. Previous study of the hypomorphic Wars2V117L/V117L mouse model found phenotypes including severely reduced fat mass, and white adipose tissue (WAT) browning, suggesting Wars2 could be a potential modulator of fat distribution and WAT browning. Methods: To test for differences in browning induction across different adipose depots of Wars2V117L/V117L mice, we measured multiple browning markers of a 4-month old chow-fed cohort in subcutaneous and visceral WAT and brown adipose tissue (BAT). To explain previously observed fat mass loss, we also tested for the upregulation of plasma mitokines FGF21 and GDF15 and for differences in food intake in the same cohort. Finally, to test for diet-associated differences in fat distribution, we placed Wars2V117L/V117L mice on low-fat or high-fat diet (LFD, HFD) and assessed their body composition by Echo-MRI and compared terminal adipose depot weights at 6 months of age. Results: The chow-fed Wars2V117L/V117L mice showed more changes in WAT browning marker gene expression in the subcutaneous inguinal WAT depot (iWAT) than in the visceral gonadal WAT depot (gWAT). These mice also demonstrated reduced food intake and elevated plasma FGF21 and GDF15, and mRNA from heart and BAT. When exposed to HFD, the Wars2V117L/V117L mice showed resistance to diet-induced obesity and a male and HFD-specific reduction of gWAT : iWAT ratio. Conclusion: Severe reduction of Wars2 gene function causes a systemic phenotype which leads to upregulation of FGF21 and GDF15, resulting in reduced food intake and depot-specific changes in browning and fat mass.